Prevalence of Trichomonas spp. in domestic pigeons in Shandong Province, China, and genotyping by restriction fragment length polymorphism. (May 2016) - Jiang, Xiyue; Sun, Jingjing; Wang, Fangkun; Li, Hongmei; Zhao, Xiaomin
Highlights: The prevalence of trichomonads in pigeons in Shandong Province of China was determined. Trichomonas gallinae genotypes A and B, and Trichomonas tenax -like trichomonads were detected. Restriction fragment length polymorphism (RFLP) analyses with Bsi EI and Hae III were performed. RFLP distinguished the T. tenax -like strain from T. gallinae . Abstract: Oropharyngeal swabs ( n = 609) were collected randomly from 80, 000 domestic pigeons ( Columba livia domestica ) on five pigeon farms and at one pigeon slaughterhouse in Shandong Province, China, from September 2012 to July 2013. Trichomonas spp. were detected in 206/609 (33.8%) samples. The prevalence was 14.9–31.1%, depending on different levels of sanitation and management, and was 4.8% in nestling pigeons, 13.6% in breeding pigeons and 35.2% in adolescent pigeons. Trichomonas gallinae genotypes A and B, and Trichomonas tenax -like isolates were identified by PCR-restriction fragment length polymorphism (RFLP) analysis and sequencing of the 5.8S rDNA-internal transcribed spacer (ITS) regions. RFLP analysis with the restriction enzyme Bsi EI generated different RFLP band patterns between T. gallinae and T. tenax -like isolates. When Bsi EI RFLP analysis was combined with Hae III RFLP analysis, all infection types of T. gallinae and T. tenax -like isolates could be identified.